Bacon hogs - Bottomly, Herbert Jefferson (My University, 1906)
Introduction: If there is one class of farm animals that is misunderstood, undervalued, and uninvestigated by the majority of farmers in the United States, both in the corn belt and out of it, it is the bacon hog. Investigation shows that the unfavorable light in which the bacon hog is viewed is due largely to an attempt on the part of the farmer to consider the bacon hog from a strictly lard producing standpoint. The bacon hog is designed for the production of bacon and it is most important that they should not lay on fat as do the lard producing hogs. The bacon hog is a pure bred animal in fact the principle breed of bacon hogs, is one of the oldest, breeds of hogs known. They are bred for the economical production of bacon of the highest class, and as high grade bacon has a large proportion of lean meat to fat consequently a bacon hog must produce much more lean meat than fat. This point has been kept well in mind in the developing of the breeds of this class, and as a result a hog has been obtained that differs in many respects from the so called mortgage lifter of the corn belt and certainly will not fill all the qualifications of the fat hog classes. And best results from them cannot be obtained under conditions in which the fat hog gives the best returns. That the men who have been handling the bacon hog knew what they were about, is shown by the following standard of excellence as adopted by the national Pig Breeders Association of Great Britain; the Tamworth being the leading breed of bacon hog.
Citation: Bottomly, Herbert Jefferson. Bacon hogs. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Animal Husbandry; Bacon Hogs; Tamworth Hog; Theses